The Influence of Firm Size, Corporate Governance, Green Accounting Disclosure on Sustainability Report Disclosure and Financial Performance and Its Impact on Value Company - Karsam, Karsam; Sasmita, Jenny; Hudin, Norlaile Salleh; Rainanto, Bambang Hengky; Solihin, Solihin; Noor, Basyiruddin (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2022)
The importance of the company to maintain the continuity of its business in the future becomes a very crucial issue at this time, the Company must pay attention to the planet, people and profit. The purpose of this study was to determine the effect of Company Size, Corporate Governance Disclosure of Sustainability Report and Financial Performance as well as its impact on the Company's Corporate Values in Mining Companies listed on the Indonesia Stock Exchange. Samples are determined based on purposive sampling technique, with a total sample of 15 companies. The study used secondary data obtained from the Indonesia Stock Exchange website in the form of financial statements from 2011-2021. The hypothesis in this study using path analysis with smart pls. The results show that Company Size and Corporate Governance influence the green accounting disclosure and sustainability report disclosure, then sustainability report disclosure influences Financial Performance and has an impact on the Company's Value in Mining Companies listed on the Indonesia Stock Exchange during 2011-2021. This means that the frequent meetings of the board of directors and the audit committee as indicators of Corporate Governance will produce effective decision making in disclosure of sustainability reports and Financial Performance as measured by profitability will provide management motivation in reporting important information for the company's sustainability to increase the company's value.